Phenotypic detection of extended spectrum ?-lactamase and AmpC ?-lactamase in urinary isolates of Escherichia coli at a tertiary care referral hospital in Northeast India - Bora, A; Ahmed, GU; Hazarika, NK (Journal of College of Medical Sciences-Nepal, 2013)
Objective Urinary tract infections (UTIs) are the most prevalent infections worldwide, mostly caused by Escherichia coli. Emerging antibiotic resistance due to extended spectrum â-lactamase (ESBL) and AmpC β- lactamase production limit the use of β-lactam antibiotics against the infections caused by E. coli. We detected the production of ESBL and AmpC β-lactamase in urinary isolates of E. coli, recovered from a tertiary care referral hospital in Northeast India. Materials and Methods A total of 140 E. coli urinary isolates were recovered during October 2008 to January 2009. Antibiotic susceptibility testing and ESBL detection were carried out according to Clinical Laboratory and Standards Institute (CLSI) guidelines. Phenotypic detection of AmpC β-lactamase was carried out by AmpC disc method. Results Among the 140 urinary isolates, 112 isolates (80%) were multi-drug resistance (MDR). ESBL was detected in 67.14% (94/140) of E. coli isolates. AmpC β-lactamase was detected in 22.34% of ESBL producing E. coli isolates. Conclusions Routine testing for ESBL and AmpC β-lactamase in E. coli urinary isolates with conventional antibiogram would be useful for strict antibiotic policy implementation in hospitals, to estimate the impact of increased drug resistance and to take steps for reducing their resistance. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 22-29 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8682